Studi Kasus Penggunaan Sumber Daya Air di Daerah Aliran Sungai (DAS) Way Ketibung Kabupaten Lampung Selatan - Sumiharni Sumiharni; Amril Ma'ruf Siregar; Karina H Ananta (UNIVERSITAS LAMPUNG, 2016)
The location of the watershed that becomes the subject of study is the Way Ketibung watershed, which the part of Sekampung watershed and administratively located in South Lampung district. The objective of the study is to analyze and predict water utilization for current condition and for the needs in the year 2019 and 2024 in Way Ketibung watershed South Lampung district. In this study, water utilization that’s being analyzed is water use in irrigation and domestic Water use will be compared with water availability in Way Ketibung watershed. Water discharge analy- sis is used FJ. Mock method. The result from the analysis shown that Way Ketibung watershed has an average water discharge 4,228 m3/second. The water discharge of Way Ketibung watershed capable to fulfill water use in irrigation, which on average for 2,1773 m3/s and also fulfill domes- tic water use until the year 2024 which the population being projected 144.496.